Teamwork makes the dream work: group effectiveness in a “Paper Chase” collaborative writing exercise for higher education - Moxie, Jessamyn; Dahl, Alicia A.; Fernandez-Borunda, Alejandra; Partridge, Hannah (Frontiers in Education, 2025)
IntroductionCollaborative writing produces higher-quality products and promotes other skills, such as problem-solving, that may assist in team science and employment among higher education students. Opportunities for supportive, cooperative learning and writing may be limited for students. The Paper Chase program is a structured exercise for rapidly disseminating research findings through facilitated, collaborative writing. To support skill development in collaborative writing, we examine group effectiveness within the Paper Chase program. Our facilitation and research teams included both faculty and graduate students.MethodsWe conducted pre-and post-questionnaires among participants in a Paper Chase event among 25 participants unfamiliar with one another prior to the exercise. We analyzed closed-ended responses using descriptive statistics and paired t-tests. Open-ended responses were analyzed using a content analysis approach.ResultsFindings show increases in positive attitudes toward teamwork, improvements in self-confidence, and collaborative skills (e.g., interpersonal communication). The structure of Paper Chase supported growth in teamwork abilities but also challenged some participants in their time management (e.g., need for mentoring) and breaking from individual-focused patterns.DiscussionThis approach is promising for other academic environments, including familiar and unfamiliar research teams.